Pengaruh Prosedur dan Perencanaan Produksi terhadap Ketaatan dan Kepatuhan Pencapaian Kinerja - Joni Hendra (Ecobuss, 2015)
The study on PT. Keramik Paolo, focusing on the implementation of procedures production there in will use the planning production of the report as a benchmark for the achievement of a planning while implementing production procedures are going well. The method is qualitative descriptive research to procedure production, and quantitative descriptive. The study is to determine the relationship between the planning productions with the achievement of the company's production. The procedure production at PT. Keramik Paolo run by 9 function, namely the PPC, production, casting parts, finishing parts, selecting parts, glaze parts, painting parts, loading parts and grading section. Despite all the activities performed by the ninth function has the same objective, namely the production order fulfillment, but each function has each procedure in the realization of planning production. The implementation of procedure production at PT. Keramik Paolo outlines are already well underway in accordance with standard operating procedures that have been established, although there are still some parts of production have not been able to carry out the procedure with a good production. Addition of Quality Control section in the production procedure of PT. Keramik Paolo is one of the author's suggestion to improve the smoothness of the production process and can also be used as one of the measures to enhance internal control systems in the procedure production. Keywords: implementation, procedures production, adherence and compliance, performance